Pengaruh Pendidikan Kesehatan dan Pemberian Daun Salam Pada Pasien Dengan Asam Urat di Wilayah RT 10 Kelurahan Murni - zuli Nuranti; Maimaznah Maimaznah; amelia ade anggraini (Jurnal Abdimas Kesehatan (JAK), 2020)
Gout is a very painful arthritis caused by the accumulation of crystals in the joints, due to high levels of uric acid in the body. Joints that are attacked primarily are the toes, knees, heels, wrists, fingers and elbows. Apart from pain, gout can also make the joints swell, inflamed, hot and stiff so that sufferers can not do activities as usual. Management of gout is divided into three namely pharmacologically, non-pharmacologically and herbal. Management of gout in non-pharmacological salam plants (Syzygium polyanthum Wight). Salam plants contain tannins, flavonoids, alkaloids, and essential oils consisting of citrate and eugenol. Bay leaf can increase urine production (diuretic) so that it can reduce blood uric acid levels. Based on the assessment conducted through interviews, observations and questionnaires obtained data in RT 10 Kelurahan Murni with a KK number of 47 with 172 population, namely the elderly with gout 9.0 20 20%. The activity starts at 15:45 WIB and ends at 16:30 WIB. The activity was carried out not according to the plan that had been made because residents who came one by one and many were still waiting for other residents to come to the extension site. The activity starts with the participants coming by filling in the attendance sheet then the participants are directed to sit in the classrooms of SD N 174 to attend counseling about gout. The results of the participants' education were able to explain again the meaning of gout 80.5%, the cause of gout 78.0%, signs and symptoms of gout 90.2%, prevention of gout 90.2% and complications of gout 78.0% .